IDENTIFICATION OF Acacia mangium PROVENANCES FOR SOLID-WOOD FOREST PLANTATIONS - Nurhasybi Nurhasybi; Dede J. Sudrajat; Komar Diatna (Indonesian Journal of Forestry Research, 2009)
Provenance trial is a planting test aimed at ﬁ nding the best provenance for establishing forest plantations. Such best provenance depends on the type of ﬁ nal harvest or yield expected.  The objective of this research was to identify A. mangium provenances that were suitable for forest plantation producing solid woods for construction and furniture. A total of 225 samples of 15 provenances from Papua New Guinea and Australia were planted in three blocks in Parungpanjang, Bogor, West Java. The measured parameters included tree height, clear bole height, stem diameter, tree volume, stem form, branching habit, and crown form. Bi-plot analysis indicated that Kini WP, Keru Village WP, Derideri R. Morehead, and Claudia River were the best provenances in terms of productivity. Correspondence analysis showed that almost all provenances were equally good in stem form, but they varied in branching system as well as crown form.  Provenances Kini WP, Keru Village WP, Kiriwo/Serisa WP, and Bimadebun Village possessed the better branching habit.  In terms of crown form provenances Dimisi Village WP, Kiriwo/Serisa WP, and Derideri R. Morehead exhibited a good performance. In general, ﬁ ve provenances, i.e. Kini WP, Keru Village WP, Derideri R. Morehead, Kiriwo/Serisa WP, and Claudia River were considered appropriate for seed sources supplying seeds for industrial plantation development intended to produce construction and furniture material.